PERFORMA BEBERAPA GALUR AYAM LOKAL FASE GROWER YANG DIPELIHARA PADA TIPE LANTAI KANDANG BERBEDA - Julius Porimau; Bercomien J. Papilaya; Muhammad J. Wattiheluw; Rajab Rajab (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
This research aims was to know effect of the interaction between breed and cage floor type factors on the performance of native chickens. The materials used in this study were three breeds of native chickens on grower phase with total number of 72 tails of chicken, an average age was 8 weeks, and an average live body weight was 408.98 grams. The research method used was factorial completely randomized design 3 x 2 x 4. Breeds factor consisting of G1 = Arabian chicken; G2 = Kampung Super, and G3 = Kampong chicken. While the factor of the floor type of cage consists of both L1 = slat floor and L2 = litter floor. Thus there are 6 treatment combinations, each combination treatment were repeated 4 times and each replication consists of 3 chickens, so there are 72 chickens as the unit of observation. The variables observed included feed consumption, drinking water consumption, average daily gain, and feed conversion. The results showed that the interaction between grooves and floor types were not significantly different for all observed variables. Chicken breeds showed significant differences in feed consumption, but did not provide for water consumption, average daily gain and feed conversion. Different cage floors showed the significant difference to feed consumption and drinking water consumption, but there was not significantly different on avegrage daily gain and feed convertion of three breeds of native chicken.